In Vivo Chromatin Structure of the Murine Interleukin-5 Gene Region: A New Intact Cell System - Sanie Ymer; David A. Jans (BioTechniques)
The study of chromatin involvement in the regulation of gene expression has traditionally required the isolation of nuclei. However, cell fractionation techniques are subject to redistribution of proteins during the isolation procedure, which prevents rigorous physiologically relevant analysis. To eliminate the need to isolate nuclei and to analyze chromatin structures in vivo in response to agents regulating murine interleukin- 5 (IL-5) gene activation, we have established a novel lysolecithin permeabilized intact cell system for suspension cell types, in this case T cells. Nuclear integrity of permeabilized cells is demonstrated by nuclear transport assays using confocal laser scanning microscopy. Results are identical in unstimulated and stimulated T cells, indicating that the chromatin structure after activation is not the result of gross alterations in nuclear protein transport properties. Potential new IL-5 gene regulatory regions are identified by DNase I hypersensitivity mapping. Our lysolecithin permeabilized intact cell system is amenable to physiologically relevant analysis of responses to signaling pathways at the level of chromatin, nuclear protein translocation and possibly other cellular functions in a variety of suspension and adherent cell types.